The feasibility in the design of small businesses. Hidromaracuya case (Ingeniería, Sostenibilidad y Sociedad, 2024)
The purpose of this project is to determine whether or not it is feasible to invest in a passion fruit production business through hydroponic cultivation, as well as to be able to design the company through design programs. This type of business has been chosen based on studies carried out in the respective markets, whose characteristics determine that it is viable to carry it out. The results indicate that there is still no massive or widespread practice of this activity, only those who carry it out, allocating large amounts of resources.The points developed in this study basically have to do with the perceptions, expectations and needs of farmers, as well as the needs they have and the market segments of which they are part.
Keywords: design; hydroponics or hydro cultivation; granadillas